DRUG LEGALIZATION IN FEDERALIST CONSTITUTIONAL DEMOCRACIES the canadian cannabis case study... in comparative context. - Alati, Daniel, 1986- ([S.l.] : ROUTLEDGE, 2022)
This book uses the Canadian cannabis legalization experiment, analyzed in the historical context of wider drug criminalization in Canada and placed in an international perspective, to examine important lessons about the differential implementation of federal law in jurisdictions within federalist constitutional democracies. Utilizing a socio-legal, interdisciplinary methodology, the work provides a comprehensive history of Canada's federal drug policy and engages in a critical appraisal of its provincial implementation. It also presents a significant international and comparative component, bringing in analyses of the status of drug legalization in other federalist constitutional democracies. Readers of the book will thus gain a comprehensive knowledge of drug legalization in federalist constitutional democracies. They will also better understand the political and cultural factors that impact upon differential implementation of federal law in individual jurisdictions, including, but not limited to, legacies of racism and stigmatization of drug use. Using the experience of Canada and other countries, future challenges and lessons to be learned for states considering federal drug legalization are analyzed and explained. The book will be a valuable resource for students, academics and policy-makers in the areas of Criminal Law, Constitutional Law, Criminology, Socio-Legal Studies, Indigenous Studies, and Drug and Health Policy Studies.
OCLC-licensed vendor bibliographic record.
Keywords: LAW / General; LAW / Administrative Law & Regulatory Practice; LAW / Comparative; Narcotic laws -- Canada; Drugs of abuse -- Law and legislation -- Canada; Drug legalization -- Government policy -- Canada; Drug control -- Canada; Narcotic laws; Drug legalization